Synthesis and Characterization of Poly (Ester‐Imide) S Based on Imide Dicarboxylic Acid with Dihydroxy Heterocyclic Compounds - Baqer Hussein , Nadia (Medical Science Journal for Advance Research, 2024)
By using dibutyltine dilaurate as a catalyst in the polycondensation of imide dicarboxylic acid and aromatic diols, two thermally stable and organosoluble poly(ester-imide) s were created. One mole of orthochlorobenzaldehyde and 2,4-dichlorobenzaldehyde was condensed, respectively, with p-hydroxy acetophenone to yield two phenolic compounds. Two Imide compounds were prepared from the reaction of Pyromellitic anhydride, and 3,3,4-benzophenone tetracarboxylic dianhydride with anthranilic acid respectively. The structural properties of the poly (esters-imide)'s were verified by FTIR, 1H NMR, and 13C NMR spectroscopy analysis of the synthesized polymers.